Entropy variation in isothermal fluid flow considering real gas effects - da Silva, Maurício Guimarães; de Oliveira, Paulo Afonso Pinto [UNESP] (FapUNIFESP (SciELO), 2011)
The present paper concerns on the estimative of the pressure loss and entropy variation in an isothermal fluid flow, considering real gas effects. The 1D formulation is based on the isothermal compressibility module and on the thermal expansion coefficient in order to be applicable for both gas and liquid as pure substances. It is emphasized on the simple methodology description, which establishes a relationship between the formulation adopted for ideal gas and another considering real gas effects. A computational procedure has been developed, which can be used to determine the flow properties in duct with a variable area, where real gas behavior is significant. In order to obtain quantitative results, three virial coefficients for Helium equation of state are employed to determine the percentage difference in pressure and entropy obtained from different formulations. Results are presented graphically in the form of real gas correction factors, which can be applied to perfect gas calculations.
Keywords: Entropy; Isothermal flow; Petroleum engineering; Real gas; Computational procedures; Correction factors; Entropy variation; Equation of state; Flow properties; Ideal gas; Isothermal compressibility; Isothermal fluid flow; Perfect gas; Pressure loss; Pure substances; Quantitative result; Real gas effects; Thermal expansion coefficients; Variable area; Virial coefficient; Equations of state; Flow of fluids; Helium; Professional aspects; Real variables; Thermal expansion; Transport properties; Gases